Fostering improved terms of trade for ACP states : an evaluation of the European Union's Green Paper - Alleyne, Frank W. (1998)
Presents an overview of the Green Paper and evaluates selected key conceptual issues which permeate the thinking documented. Assesses the trade performance of the ACP states in Lomé, calling particular attention to the Special Protocols. Evaluates the fundamental shift in philosophy which is occuring and its implication for ACP states development. Addresses trade development as opposed to trade liberalization in developing countries. Provides a critique of the reform options presented by the European Union and suggests policies for enhancing capacity in ACP states.